Estudo da fragilidade em fêmures de ratos diabéticos pela análise densitométrica e biomecânica - Manaia, Cristiane Nalin [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Diabetes é uma desordem metabólica que interfere no tecido ósseo. Objetivou-se avaliar a fragilidade de fêmures de ratos diabéticos tipo 1 (DM1), pela densitometria e ensaio biomecânico. Foram utilizados 22 animais (Rattus novegicus, albinus, Wistar), com aproximadamente 250 gramas, divididos em grupo: Controle e Diabetes aleatoriamente. A DM1 foi inoculada pela estreptozotocina dissolvida em tampão citrato a 0,01M, pH 4,5, na concentração de 35mg/Kg na via peniana. Após 4 semanas da indução, foram sacrificados e os fêmures desarticulados. Para análise densitométrica utilizouse densitômetro DPX Lunar ™, para densidade radiográfica o sistema digital Digora®. No ensaio mecânico usou a máquina universal de ensaio EMIC® na região diafisária do fêmur. Os resultados passaram por análise estatística, teste t de Student, paramétrico e não pareado, onde o Conteúdo Mineral Ósseo (g), Densidade Mineral Óssea (g/cm²), Densidade Óssea (mmAl), Força Máxima (N) observadas nos fêmures de portadores de diabetes foi inferior ao grupo controle comprovado estatisticamente. Na Rigidez (x103N/m) e na Área (cm²) não houve diferença estatística. Conclui-se que o diabetes tipo 1 causou fragilidade nos fêmures dos ratos, reduzindo sua densidade mineral e consequentemente sua resistência mecânica.

Diabetes is a metabolic disorder that interferes with bone mass reducing the minerals density and consequently its mechanical strength. Our objective was to evaluate the femurs fragility in rats with type 1 diabetes (DM1)by densitometry and biomechanical tests. A total of 22 animals (Rattus novegicus, Albinus, Wistar), with approximately 250 grams were divided into group: Control and Diabetes. In-group Diabetes animals received streptozotocin dissolved in citrate buffer 0.01 M, pH 4.5, at a concentration of 35 mg/kg single dose in the penile vein. After 4 weeks of induction, the animals were sacrificed and the femurs were disarticulated for biomechanical analysis (Maximum Strength and stiffness) and densitometric analysis (Bone Mineral Density, Bone Mineral Content and Area). For densitometric analysis was used densitometer Lunar DPX ™ for the radiographic density digital Digora®. The biomechanical analysis used the universal testing machine EMIC ® in the femoral shaft. The results passed through statistical analysis, Student t test, parametric and nonpaired where of bone mineral content (g), bone mineral density (g/cm²), Bone Density (mmAl) Maximum Force (N) observed in the femurs of diabetic patients was lower than the control group accused significative differences. In Stiffness (x103N/m) and Area (cm²) there was no statistical difference.. Concluded that type 1 diabetes has caused weaknessin the femurs of mice, reducing its mineral density and consequently its mechanical strength.
Keywords: Diabetes; Densidade óssea; Diabetes mellitus tipo 1; Estreptozocina; Bone density; Diabetes Mellitus, Type 1; Streptozocin